IMPACT OF CASHLESS POLICY ENFORCEMENT AND NAIRA REDESIGN ON FRESH CATFISH MARKETING IN MAKURDI LOCAL GOVERNMENT AREA OF BENUE STATE, NIGERIA - Soom, A.; Humbe, I.T.; Musa, A. U. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study examined the impact of Cashless Policy Enforcement and Naira Redesign on Fresh Catfish Production and Marketing in Makurdi Local Government Area of Benue State, Nigeria. Multi-stage sampling procedure was employed to select 100 respondents for the study. Data were collected with the aid of structured questionnaire and analyzed using descriptive statistics and farm budgeting techniques. The result revealed that fresh catfish producers were in their productive age with mean age of 34years. Majority (76%) of the fresh catfish producers were males and 84% married. The average household size and farming experience were 5 persons and 6 years, respectively. The results of the profitability analysis of catfish marketing in the study area before and during the cashless policy enforcement and Naira redesign revealed that before the policy, the catfish producers’ total variable costs and total fixed costs were N1701379 and N665689.22, respectively, making a total cost of N2367068.22. The results further revealed that total revenue of N2659284.66 and a net farm income of N292216.440 were realised. The profitability ratio shows that for every one naira invested, the catfish producers made about 89 kobo. However, the result revealed that, amid the cashless policy enforcement and Naira redesign, the total variable cost and total fixed cost were N827791.66 and N712688.47, respectively, making a total cost of N1540475.13. The results revealed total revenue of N1650800 and a net farm income of N110384.87. The profitability ratio shows that for every one naira invested, the catfish producers made about 92 kobo. The result of the impact of catfish marketing on the income level of the marketers in the study area before and during the cashless policy enforcement and Naira redesign revealed that before the policy, 30%t of the catfish marketers had an income of over N300, 000. However, during the policy, only 26% of the catfish farmer marketers had an income of over N300, 000 and 15% had an income of less than N50, 000. The result of the constraints to catfish marketing before and during the cashless policy enforcement and Naira redesign revealed that before the policy, the most constraints to catfish marketing were high electric charges (12.3%) and lack of credit facilities (9.1%). However, during the policy, the most constraints to catfish marketing were inadequate capital (8.3%), seasonality of commodity (7.8%), high cost of feed (7.4%), high cost of production (7.3%), high cost of labour (7.3%) and low demand of product (7.0%). The study concluded that Catfish production and marketing in the study area was more profitable before the cashless policy enforcement and Naira redesign. The study recommended that provisions for agricultural incentives such as short and long-term loans, with a single digit interest rate for the marketers in order to solve the problem of lack of credit facility. Also, Marketers should form marketing cooperatives to increase their access to credit from financial institutions and hence alleviate the problem of inadequate capital.